Design Thinking in Transitional Period - Özcan, Oǧuzhan (Frontiers in Communication, 2022)
In this speculative look of design thinking through the lens of the Renaissance, the author draws our attention to the shocking similarity between the transition in today's world and the Industrial Era. In this comparison, he emphasizes the similar role of “arts in Renaissance” concept and Design Thinking. In this perspective, the author's concern is not about discussing how the Design Thinking process will be in the new era, but just speculating its role as a tool in such a transitional period.